ANALYSIS OF HOSPITAL INFORMATION MANAGEMENT SYSTEM USING HUMAN ORGANIZATION FIT MODEL - Husnaina Febrita; Martunis Martunis; Dedy Syahrizal; Munifah Abdat; Bakhtiar Bakhtiar (Jurnal Administrasi Kesehatan Indonesia, 2021)
Background: Hospital is a health care institution that provides public services for patients. It needs computerized information technology, for example, a hospital information management system.